A gluten-free diet lowers NKG2D and ligand expression in BALB/c and non-obese diabetic (NOD) mice. (9th July 2014) - Adlercreutz, E H; Weile, C; Larsen, J; Engkilde, K; Agardh, D; Buschard, K; Antvorskov, J C
Summary: The interplay between diet and immune parameters which could affect type 1 diabetes (T1D) pathogenesis is not sufficiently clarified. Intestinal up-regulation of the activating receptor natural killer group 2D (NKG2D) (CD314) and its ligands is a hallmark of coeliac disease. However, the direct effect of gluten on NKG2D expression is not known. We studied, by fluorescence activated cell sorter (lymphoid tissues) and reverse transcription–quantitative polymerase chain reaction (intestine and pancreatic islets), if a gluten-free diet (GF diet) from 4 weeks of age or a gluten-free diet introduced in breeding pairs (SGF diet), induced changes in NKG2D expression on DX5 + (CD49b) natural killer (NK) cells, CD8 + T cells and in intestinal and islet levels of NKG2D and ligands in BALB/c and non-obese diabetic (NOD) mice. Gluten-free NOD mice had lower insulitis ( P < 0·0001); reduced expression of NKG2D on DX5 + NK cells in spleen and auricular lymph nodes ( P < 0·05); and on CD8 + T cells in pancreas-associated lymph nodes ( P = 0·04). Moreover, the level of CD71 on DX5 + NK cells and CD8 + T cells ( P < 0·005) was markedly reduced. GF and SGF mice had reduced expression of NKG2D and DX5 mRNA in intestine ( P < 0·05). Differences in intestinal mRNA expression were found in mice at 8, 13 and 20 weeks. Intestinal expression of NKG2D ligands was reduced in SGF mice with lower expression of all ligands. In isolated islets, a SGF diet induced a higher expression of specific NKG2D ligands. Our data show that a gluten-free diet reduces the level of NKG2D and the expression of NKG2D ligands. These immunological changes may contribute to the lower T1D incidence associated with a gluten-free diet.